Zip file containing code and data for Curry et al. 2018 - Curry, Claire M.; Ross, Jeremy; Contina, Andrea; Bridge, Eli (Dryad Digital Repository, 2018)
Project: VARYING DATASET RESOLUTION ALTERS PREDICTIVE ACCURACY OF SPATIALLY EXPLICIT ENSEMBLE MODELS FOR AVIAN SPECIES DISTRIBUTION Accepted in Ecology and Evolution 12-Oct-2018. Versioning visible at: https://github.com/baeolophus/ou-grassland-bird-survey Please contact Claire M. Curry (cmcurry@ou.edu or curryclairem@gmail.com) about the *.R files or Jeremy Ross (jdross@ou.edu) about the point count and transect data. See README.txt for more information.